2022
DOI: 10.3389/fmicb.2022.839484
|View full text |Cite
|
Sign up to set email alerts
|

The Phlorizin-Degrading Bacillus licheniformis XNRB-3 Mediates Soil Microorganisms to Alleviate Apple Replant Disease

Abstract: In this study, an endophytic phlorizin-degrading Bacillus licheniformis XNRB-3 was isolated from the root tissue of healthy apple trees, and its control effect on apple replant disease (ARD) and how it alleviates the pathogen pressure via changes in soil microbiomes were studied. The addition of strain XNRB-3 in Fusarium infested soils significantly reduced the number of pathogens in the soil, thus resulting in a lower disease incidence, and the relative control effect on Fusarium oxysporum reached the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 128 publications
(168 reference statements)
0
5
0
Order By: Relevance
“…Additionally, the B. licheniformis XNRB-3, isolated from root tissues, exhibited enduring colonization on the roots of apple seedlings. The introduction of the XNRB-3 strain may have a prolonged growth-promoting and biocontrol influence on apple plants confronted with the challenges of ARD (Duan et al, 2022b). In this study, the colonization ability of B. amyloliquefaciens BA-4 in MR seedling rhizosphere and its biocontrol effect on ARD were evaluated in the field to verify the findings obtained from pot experiments.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, the B. licheniformis XNRB-3, isolated from root tissues, exhibited enduring colonization on the roots of apple seedlings. The introduction of the XNRB-3 strain may have a prolonged growth-promoting and biocontrol influence on apple plants confronted with the challenges of ARD (Duan et al, 2022b). In this study, the colonization ability of B. amyloliquefaciens BA-4 in MR seedling rhizosphere and its biocontrol effect on ARD were evaluated in the field to verify the findings obtained from pot experiments.…”
Section: Discussionmentioning
confidence: 92%
“…The application of phenolic acid-degrading microbes could relieve continuous cropping obstacle, such as Xanthomonas and Rhizobium (Zhou et al, 2020) and Bacillus (Duan et al, 2022) resulted in the low phenolic acid contents that contributed to soil borne disease suppression. We found that Aspergillus and Fusarium were significantly enriched in the soil amended with high concentrations of all tested phenolic acids (Table 1), indicating their potential to efficiently degrade phenolic acids (Hegde et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sectioning and Periodic Acid Schiff staining of these root samples were carried out at the Keshang Biotech Co., Ltd. (Baso Diagnostics Inc., China). And the root sections were observed and photographed using transmission electron microscope (Philips Tecnai12‐TWIN) (Duan et al, 2022). We then divided the samples into the aboveground and underground components.…”
Section: Methodsmentioning
confidence: 99%
“…as the causal agent of ARD and confirmed Fusarium solani to be one of the major pathogens (Tang et al, 2022; Xiang et al, 2022). Researchers from different demographic regions have recently exploited various control measures, such as chemical, genetic and biological measures, to alleviate ARD (Duan et al, 2022). However, genetic and biological methods are the only effective approaches to control soil‐borne pathogens in a sustainable ecological environment.…”
Section: Introductionmentioning
confidence: 99%